Development of the SiAlong Platform to Improve Digital Literacy on Landslide Disasters among Generation Z in Semarang City - Hanifah binti Mahat (Tanjung Malim, 2024)
Development of the SiAlong Platform to Improve Digital Literacy on Landslide Disasters among Generation Z in Semarang City by Hanifah binti Mahat